Vitalitas Bahasa Ternate di Pulau Hiri - Sulami Sibua; Sri Wahyuni; Adityarini Kusumaningtyas (Jurnal Ilmiah Wahana Pendidikan, 2023)
The main purpose of this study is to determine the level of condition or status of language vitality that can be directed to save a language from extinction. The general purpose of the study of language vitality is to determine the status of a language, from extinct to safe categories. The status of the language has implications for the actions that need to be taken on the language in question, whether it is necessary to do conservation, revitalization, or simultaneously conservation and revitalization. For example, conservation actions in the form of documentation can only be carried out if the language is classified as extinct or needs to be conserved and revitalized at the same time if the language is categorized as endangered or threatened with extinction. Data for the study of language vitality consists of primary data and secondary data. Primary data is data obtained directly from the source and recorded by researchers. Primary data was obtained through a list of questions in the questionnaire. Secondary data is data that is indirectly obtained from the source. For example, data is obtained from village officials and related documents. Based on the index value of each indicator, we can say that although most people on Hiri Island speak more than one language and often interact with people from different linguistic backgrounds, the use of Ternate on Hiri Island is still dominant. People on Hiri Island still use the Ternate language as a means of communication in the family and community domains. Many parents still teach the Ternate language to their children and the children can still use the Ternate language well. The Ternate language is also still used in every traditional activity on Hiri Island. However, the use of the Ternate language began to be abandoned when the community carried out bargaining activities in the realm of markets, government, and education.